Avaliação de qualidade do pão tipo francês por métodos instrumentais e sensoriais - Farias, Larissa Raphaela Gonçalves de (2012)
The French bread is the kind of bread most consumed in Brazil, being well accepted in different social and economic classes. However, this product presents very variability in their characteristics, which can result in quality problems due to lack of uniformity. For this reason, the aim of this research was to evaluate the quality of French-type bread sold in bakeries of João Pessoa-PB using sensory and instrumental methods. Initially, bread samples from twelve bakeries selected were submitted to specific volume, moisture, pH, acidity, skin color, crumb color and texture profile determinations, being all these analyses carried out in triplicate, with 10 repetitions. Subsequently, an acceptance test by a nine-point hedonic scale was applied, with 65 panelists, that evaluated the samples according to the appearance, crust color, crumb color, crust crispness, aroma, flavor, texture and overall acceptability attributes. In the instrumental tests, the main quality problems were low moisture and high acidity, as specific volume and crust lightness (L*) were satisfactory. Regarding to the sensory acceptance, 50% of the bakeries had its breads accepted in all attributes evaluated, being the lack of crispness the main quality problem found in rejected breads. The samples of one bakery were rejected also with respect to aroma, flavor and appearance attributes, presenting more necessity for improvement. Therefore, future researchs need be carried out correlating especially moist and acidity with sensorial attributes such as texture, aroma and flavor to try stablish minimum and maximum limits acceptable to thesse characteristics.